Perbedaan Efektivitas Pemberian Essensial Oil Peppermint dan Aroma Terapi Lavender terhadap Intensitas Mual dan Muntah pada Ibu Hamil Trimester I di Puskesmas Baso Kabupaten Agam Tahun 2017 - Zuraida Elsa Desria Sari (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Nausea and vomiting is a condition most often complained by pregnantwomen, especially trimester pregnant women I, where nausea vomitingexperienced by 60-80% of pregnant women. This study aims to differentiate theEffectiveness of Essential Oil Peppermint and Lavender Therapy on the Intensityof Nausea and Vomiting in Trimester Pregnant Women at Baso Health Center ofAgam District in 2017.This type of research is pre-experimental with one group pre-test-post testwit control group desgin. The population in this study were all of the firsttrimester pregnant women in the work area of Baso Puskesmas that is as many as14 people in September. Sampling using total sampling technique. Data collectionin this study used observation sheets of nausea and vomiting. Data analysisincluded univariate analysis and bivariate analysis performed by computerizationThe results showed that the essential oil peppermint was effective inreducing the intensity of nausea of vomiting with an average decrease of 5.42 andp = 0,000, giving aroma of lavender therapy is also effective against decreasednausea vomiting pregnant women with an average decrease in nausea vomiting3.28 and p = 0.001. Essential oil peppermint is more effective against decreasednausea of vomiting in pregnant women with p = 0,017.It can be concluded that the essential oil peppermint is more effectiveagainst decreased nausea of vomiting in pregnant women trimester I. For it isexpected to pregnant women to be able to use the essence of peppermint oil that ismore effective against the reduction of nausea of vomiting in pregnant women.Daftar Pustaka : 21 (2008-2016)Kata Kunci : Peppermint, aroma terapi lavender